Alcohol and Khamr in Fiqh Based on Science Perspective - MZ, Rafika Dwi Rahmah (IJISH (International Journal of Islamic Studies and Humanities), 2019)
Alcohol and khamr are compounds that we can meet every day but there are still many students and even the general public who do not understand the differences in the halal and prohibition of alcohol and khamr. Departing from this matter, this study aims as a means of education and proves the prohibition and halalness of alcohol and khamr. This article examines the views of science and the Qur'an on the prohibition and halalness of alcohol and khamr with the literature review method with a type of qualitative descriptive research. The results of this study are that khamr in Islam is intoxicating (including liquor, narcotics, psychotropic, and other dangerous drugs) whereas alcohol, not all groups can be used as ingredients for making khamr drinks. Therefore, in science, khamr and alcohol are different. Alcohol has two laws, if it is ethanol, it tends to be haram (prohibited), and other types are still considered to be halal (permitted).